Design and Implementation of a Triple Layered Commercial Security System with Arrest Bot Mechanism - MdHadiul Islam, Shayan Biswas ,GokulWarrier, A.Lavanya ,J.Divya Navamani (International Journal of Advanced Science and Technology, 2020)
There has been a plethora of research in various fields with regard to security and protection against intrusion and trespassing of all forms..Our system involves various layers of protection. At the very outset, the concerned boundary is marked with  HC-SR04 Ultrasonic sensors to detect any kind of movement towards the boundary and to detect the presence of the intruder at the second level beyond the demarcation of the HC_SR04 sensor, piezoelectric knock sensors are used which when triggered high alerts all the required alarm systems, and the unidentified intruder is then asked to stop and identify himself/herself. The intruder should posess the clearance from the headquarters to scan the QR code at the entry, and only then will that person will be allowed inside. In case he fails to register the QR code, he is asked to type the exclusive pass-code for entry. If he fails to do that as well, then he is warned and asked to leave... If there is even further detection of movement inside which can be detected using the PIR sensors, an autonomous bot is deployed which itself is programmed to avoid obstacles and reach the concerned area of breach with the help of the concerned sensors, and will immediately arrest the intruder.... As this is a micro level application with a restricted budget, this design is the best possible solution to counteract the problem but can however be applied at the macro level as possible with the proper investment.